Students’ acceptance on computer-adaptive testing for achievement assessment in Japanese elementary and secondary school - Goto, Takayuki; Kano, Kei; Shiose, Takayuki (Frontiers in Education, 2023)
The present research aimed to investigate whether Japanese elementary and secondary schools can accept computer-adaptive tests, which is an important issue under consideration for its future introduction to national achievement assessments. We conducted two studies that asked elementary and secondary school students to take a computer-adaptive test and complete the questionnaires. We assessed individual differences in achievement goals and tested whether they predicted achievement scores on a computer-adaptive test. Moreover, we asked the students about their attitudes toward different forms of tests. The study results were twofold. First, those with high performance-avoidance goals did not perform worse than those with low performance-avoidance goals after controlling for individual differences in the approach to learnings, the mediating variable. This implies that the computer-adaptive test does not reinforce students’ anxiety about test taking. Second, students did not exhibit a more negative attitude toward the computer-adaptive test than the traditional fixed-item test but had a negative perception of human-adaptive tests (tests tailored by the teacher). Our results provide practical implications that a computer-adaptive test could be carefully introduced into the national achievement assessment for Japanese elementary and secondary school children while considering their acceptance of the test.